Analysis of School Principal Leadership in Developing Effective Schools (Case Study at SMA Negeri 1 Koto XI Tarusan Pesisir Selatan Regency, Indonesia) - Yepi Herpanda; Berry Devanda; Nurhizrah Gistituati; Rusdinal; Riza Desriandi (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
The purpose of this study was to examine the effectiveness of the principal's role as a leader in managing resources in schools that have a positive impact on the creation of effective school climate in SMA Negeri 1 Koto XI Tarusan. The research used is qualitative research where the data sources or respondents are all school residents including the principal, educators and education staff, students and committees as representatives of parents in the school. Data collection techniques are observation, interviews and documentation studies of school program documents such as RKJM, RKT, and RKAS as well as documentation studies of the education unit level curriculum which contains a program of activities carried out by schools within the next one year. Data analysis used interactive models, data validity using data triangulation. The results of research conclusions The principal as a school manager is able to determine achievement targets and milestones of success in implementing the RKS which is prepared based on the education quality report card and involves various parties, both in the 4-year Medium-Term Work Plan (RKJM) and the 1-year Annual Work Plan (RKT) so that implementation of program planning is more operational and its achievements are measurable. The principal's leadership in implementing school programs must refer to programs that have been previously designed by involving school members according to their respective main tasks and functions